Pengaruh Kualitas Layanan terhadap Loyalitas Wisatawan Nusantara dengan Kepuasan Wisatawan Nusantara sebagai Variabel Intervening - Eny Sulistyowati; Sobirin Maliyan (Jurnal Maksipreneur, 2015)
In the business world, customer satisfaction is an absolute must be the goal to achieve success. Due to the achieved satisfaction of the consumers or customers will bring many benefits to manufacturers or institutions, among others, will make consumers become loyal. From the results of research conducted shows that Quality of services provided to tourists have a strong influence on the loyalty of tourists to visit the tourism objects in the area of Yogyakarta. This is evidenced by the results of the r2 of the influence of service quality to local tourists loyalty is about 22.2%. This shows if the service quality provided by the tourism industry in Yogyakarta enhanced within the region will make the travelers loyal to the tourism industry in Yogyakarta. In addition to the quality of services provided to tourist there are other factors that also have a strong influence on the tourist loyalty that tourist satisfaction factor, as evidenced by the r2 value of 15.2%. This suggests that if the tourism industry pay attention to things that could improve the satisfaction of tourists visiting the attractions in Yogyakarta, then the tourists will be eager to visit again or loyal. Meanwhile, indirectly influence the quality of service to tourists loyalty through the satisfaction of tourists who visit tourist attraction in the DIY region have only r2 values of 0.015 or 1.5%. This implies that the satisfaction of tourists is less strong loyalty of tourists who visit tourist attraction in the area of DIY.